Boceprevir and telaprevir‐based triple therapy for chronic hepatitis C: virological efficacy and impact on kidney function and model for end‐stage liver disease score. Issue 9 (25th February 2014) - Virlogeux, V.; Pradat, P.; Bailly, F.; Funingana, G.; Gonçalves, F.; Maynard, M.; Hartig‐Lavie, K.; Amiri, M.; Zoulim, F.
Summary Triple therapy using telaprevir or boceprevir [hepatitis C virus (HCV)‐NS3/NS4A protease inhibitors (PI)] in association with PEG‐IFN/ribavirin has recently become the new standard of care (SOC) for treatment of HCV genotype 1 patients. Our objective was to assess the efficacy and tolerance of triple therapy in routine clinical practice. A total of 186 consecutive HCV patients initiating triple therapy were enrolled in a single centre study. Clinical, biological and virological data were collected at baseline and during follow‐up as well as tolerance and side effect details. Among 186 HCV patients initiating triple therapy, 69% received telaprevir and 31% boceprevir. Sixty‐one per cent of patients had cirrhosis. The overall extended rapid virological response (eRVR) rate and sustained virological response (SVR) rate were 57.0% and 59.7%, respectively. IL28B CC phenotype was associated with increased probability of achieving eRVR and SVR, whereas previous non‐response was associated with low eRVR and SVR rates. The SVR rate increased from 30.8% in previously non‐responders to 59.1% in partial non‐responders and 75% in relapsers. SVR rate in naive patients was 62.5%. Glomerular filtration rate assessed by MDRD after 12 weeks of therapy was significantly reduced for both PI (P < 0.001). The model for end‐stage liver disease (MELD) score was significantly increased at W12 for telaprevir (P = 0.008) and at W24 for boceprevir (P = 0.027). PI‐based triple therapy leads to high rates of virological response even in previously non‐responder patients. Renal function after triple therapy is impaired as well as MELD score in all patients. Cautious clinical monitoring should focus not only on haematological and dermatological side effects but also on renal function.